The effect of cementite size and morphology on the abrasive wear behavior of UHC steel - Ozdemir, Niyazi; Sarsilmaz, Furkan; Orhan, Nuri (Asme-Amer Soc Mechanical Eng, 2008)
In this study, the abrasive wear behavior of a grain refined hypereutectoid carbon steel containing 1.2% C, 4% Al, 0.20% Mo, and 0.1% Ti was investigated experimentally. Thermal cycles were applied to all specimens about ten times to obtain a fine-grained structure and to gain more softness structures, such as spheroidized cementite for these steels. After every thermal cycle, the microstructures of specimens were examined by scanning electron microscopy to determine the transformation mechanism of structure. Microstructure analyses showed that size of cementite decreased as a function of heat treatment cycle. With the increase of heat treatment cycle, the grain size of cementite in all specimens started to decrease. As a consequence, these cementite islands transformed to spherical cementite having an average grain size of 5 mu m. In addition, the wear test results indicated a correspondence between wear rate and thermal cycling. However, the hardness values decreased with increasing heat treatment cycle.
Keywords: hypereutectoid steel; thermomechanical treatment; abrasive wear